DESIGN PELUBANG PLASTIK MULSA DENGAN SISTEM ELEKTRIK - Rachmawati, Putri; Mirza Yusuf (Politeknik Negeri Cilacap, 2024)
The purpose of this study was to lighten rice farmers and chili farmers so that there are no complaints of fatigue, joint pain because in perforating plastic it takes a long time to perforate. This tool method uses an electrical system which uses battery indicators and diameter sizes of 0.05 cm, 0.06 cm and 0.07 cm, so that it can make it easier for farmers according to the size to be used. This study was designed with an electrical system using 4 lithium batteries. The level of effectiveness of the resulting time in plastic holes with an area of 12 m2 is 10 minutes for 70 plastic holes.